Predictors of outcome after a time-limited psychosocial intervention for adolescent depression - Parhiala, Pauliina; Marttunen, Mauri; Gergov, Vera; Torppa, Minna; Ranta, Klaus (Frontiers in Psychology, 2022)
Research on the predictors of outcome for early, community-based, and time-limited interventions targeted at clinical depression in adolescents is still scarce. We examined the role of demographic, psychosocial and clinical variables as predictors of outcome in a trial conducted in Finnish school health and welfare services to identify factors associating to good outcome after a brief depression treatment. A total of 55 12–16-year-olds with mild to moderate depression received six sessions of either interpersonal counseling for adolescents (IPC-A) or brief psychosocial support (BPS). Both interventions resulted in clinical improvement at end of treatment and 3- and 6-month follow-ups. Main outcome measures were self-rated BDI-21 and clinician-rated Adolescent Depression Rating Scale (ADRS). Latent change score (LCS) models were used to identify predictors of change in depressive symptom scores and clinical remission at end of treatment and 3-month and 6-month follow-ups over the combined brief intervention group. Symptom improvement was predicted by younger age and having a close relationship with parents. Both symptom improvement and clinical remission were predicted by male gender, not having comorbid anxiety disorder, and not having sleep difficulties. Our results add to knowledge on factors associating with good treatment outcome after a brief community intervention for adolescent depression. Brief depression interventions may be useful and feasible especially for treatment of mild and moderate depression among younger adolescents and boys, on the other hand clinicians may need to cautiously examine sleep problems and anxiety comorbidity as markers of the need for longer treatment.